Bundle sheath cell-dependent chloroplast movement in mesophyll cells of C4 plants analyzed using live leaf-section imaging - Yuta Kato; Takao Oi; Yoshikatsu Sato; Mitsutaka Taniguchi (Scientific Reports)
Abstract C4 plants have C4 photosynthetic cycle, a CO2-concentrating pump that functions across mesophyll (M) and bundle sheath (BS) cells. M chloroplasts aggregate toward BS cells in response to environmental stress, which would contribute to adjustment in C4 photosynthetic cycle. However, it remains unclear whether M chloroplast movement is an intercellular response mediated by BS cells. One major challenge to resolve this is the difficulty in observing chloroplast movement due to scattering and absorption of observation light in live-leaf tissues. We established a live leaf-section imaging technique that enables the long-term observation of sections of chemically unfixed leaf blades, with which we quantitatively analyzed M chloroplast movements. Another challenge in clarifying the contribution of BS cells to M chloroplast movement is the selective ablation of BS cells without impairing M cell function. To investigate the necessity of BS cells for M chloroplast movement, we developed a method to remove BS cells only based on differences in shape between M and BS cells. We also found that chloroplasts in M cells without adjacent BS cell contents did not show typical aggregative movement. This indicates that the M chloroplast aggregative movement occurs during communication with BS cells.